2019
DOI: 10.1097/sla.0000000000002661
|View full text |Cite
|
Sign up to set email alerts
|

Mini- or Less-open Sublay Operation (MILOS): A New Minimally Invasive Technique for the Extraperitoneal Mesh Repair of Incisional Hernias

Abstract: The MILOS technique allows minimally invasive transhernial repair of incisional hernias using large retromuscular/preperitoneal meshes with low morbidity. The technique combines the advantages of open sublay and the laparoscopic IPOM repair.ClinicalTrials.gov Identifier NCT03133000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 18 publications
2
53
0
15
Order By: Relevance
“…This hampers comparability of the study findings on RD. Recently, numerous innovative techniques, with case series reports, have been introduced for surgical treatment of RD (4, 619). Classification of RD is needed in order to be able to evaluate the significance of all these different techniques and to properly characterize the respective patient collective in comparative studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hampers comparability of the study findings on RD. Recently, numerous innovative techniques, with case series reports, have been introduced for surgical treatment of RD (4, 619). Classification of RD is needed in order to be able to evaluate the significance of all these different techniques and to properly characterize the respective patient collective in comparative studies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current literature, no clear distinction can be made in the recurrence rate, postoperative complications, or patient reported outcomes (2). This applies, in particular, to the numerous innovative minimally invasive techniques recently reported in the literature for treatment of RD with concomitant ventral hernias (4, 619). The promising results of new procedures with extraperitoneal mesh placement and anatomical restoration of the linea alba, such as the endoscopic-assisted or endoscopic mini open sublay repair (MILOS, EMILOS), endoscopic-assisted linea alba reconstruction (ELAR), laparoscopic linea alba stapler repair, enhanced total extraperitoneal ventral hernia repair (eTEP), laparoscopic intracorporeal rectus aponeuroplasty (LIRA), preaponeurotic endoscopic repair (REPA) and totally endoscopic sublay (TES), have to be confirmed in future trials (4, 619).…”
Section: Introductionmentioning
confidence: 98%
“…However, conventional open sublay surgery requires a large midline incision, which may involve complications such as large tissue trauma, postoperative pain, and wound infection. Several novel extraperitoneal techniques have been developed to perform retromuscular repair through minimally invasive methods, including mini/ less open sublay (MILOS) repair [9], followed by modified Fig. 7 Placement of a 15 × 9-cm 2 self-gripping mesh in the extraperitoneal space (a case of umbilical hernia) MILOS surgery with endoscopic assistance (e-MILOS) [10], laparoscopic transabdominal retrorectus repair [11], endoscopic transabdominal midline reconstruction technique facilitated by endoscopic linear stapling [12], completely endoscopic sublay dissection methods including the enhanced-view totally extraperitoneal (eTEP) technique initiated by Belyansky et al [13], and the TES repair technique reported by our team [2].…”
Section: Discussionmentioning
confidence: 99%
“…ретромускулярная пластика) и «eTAR» (endoscopic transversus abdominal release -эндоскопическая задняя сепарация поперечных мышц) [21,22]. В 2015 г. немецкими хирургами J. Schwartz и R. Bittner [23,24] [25,26]. Стремительное распространение эндовидеохирургических методов привело к возникновению в последние годы новых вариантов хирургического лечения при вентральных грыжах: TARUP (англ.…”
Section: Introductionunclassified
“…В более поздних работах W. Reinpold и соавт. (2019) [26] констатируют, что пупочная или эпигастральная грыжа диаметром более 1,5 см даже без диастаза может быть прооперирована с помощью этой методики.…”
Section: Introductionunclassified